Comparative Evaluation of IRI Predictions Using MEPDG 2015 with New Mexico and Virginia Local Calibrations in Indonesia - Yuliani, Gita; Hariyadi, Eri Susanto; Sjafruddin, Ade (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study aims to evaluate the accuracy of IRI prediction using the MEPDG 2015 method with two different local calibration parameters—New Mexico and Virginia—by comparing them against actual field conditions in Indonesia. The analysis was conducted on six segments of the North Coast National Road (Pantura), totaling 55.87 km, using input data from 2020 and field measurements from 2021 to 2023. Pavement responses were analyzed using ELMOD 6 and KENPAVE, and predictions were made for rutting, fatigue cracking, and IRI. The results showed that MEPDG 2015 with Virginia calibration produced the smallest relative deviation (?15.66%) compared to the field data, indicating better alignment with actual pavement performance than the New Mexico calibration. The findings confirm the importance of selecting calibration parameters appropriate to local climate and structural conditions. MEPDG 2015 with Virginia calibration is recommended for future IRI prediction in areas with similar environmental characteristics to western Indonesia. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and Production